INFORMATION SYSTEM DESIGN IN WAREHOUSE INVENTORY CONTROL - Wiku Larutama; Anisa Putri Rahmadani Lubis; Adelia Suyatno; Nabilah Hana Camellia (Journal of Logistics and Supply Chain, 2023)
Inventory management is a crucial aspect for the smooth operation of businesses, as the availability of stock significantly impacts the company's operations. Supporting successful inventory management involves utilizing an information system that assists the company in monitoring inventory in real time and presenting accurate and up-to-date information. The purpose of conducting this research is to comprehend the concept of inventory control and its interrelation with an information system. The stage of this research is to carry out a research framework starting from planning, designing until the system can be used by users. In addition, the results of a literature review that was conducted using data from earlier studies by other researchers were used. The role of information systems in inventory control is of paramount importance, as it can enhance effectiveness and efficiency by providing real-time data about warehouse stock, thereby reducing the risk of errors that could result in losses for the company. Therefore, the development of an inventory control information system is anticipated to alleviate issues related to inventory management within the company.